BPN's Role in Settlement of Compensation at Rail Bordering in The Joglo Area - Tony Rizky Herlambang; Marisa Kurnianingsih (Universitas Muhammadiyah Surakarta, 2023)
This research aims to find out the role of BPN and the internal and external obstacles encountered in the process of providing compensation. Compensation or compensation is a principle where the sale and purchase of land will be fair if the compensation is the same as what would have been incurred without buying government land. This research uses an empirical juridical method, namely researching real events in society. It can be seen that the role of BPN is as an implementer in the process of providing compensation. The internal obstacles encountered were inherited land for which there was no inheritance certificate and collecting the identities of the heirs. External obstacles are about people who object to the amount of compensation which is considered not in accordance with the wishes of the community.